Paclitaxel-induced acute fibrinous and organizing pneumonitis in early breast cancer: A case report - Piyarat Limpawittayakul; Supinda Petchjorm; Worawong Chueansuwan; Wanvisa Boonfueang (Respiratory Medicine Case Reports, 2024)
Background: Paclitaxel is a chemotherapeutic drug widely used in breast cancer treatment. While common side effects are possible, paclitaxel-induced pneumonitis is rare, with an estimated incidence of 1%–5% and a high mortality rate. Case presentation: A 57-year-old Thai woman diagnosed with stage II right breast cancer. She received adjuvant chemotherapy comprising doxorubicin and cyclophosphamide, followed by weekly paclitaxel. After the ninth paclitaxel cycle, she developed acute respiratory failure. Transbronchial biopsies revealed acute fibrinous and organizing pneumonitis. The patient was placed in prone position. Following the administration of dexamethasone, her symptoms improved. However, while reducing the dexamethasone dosage, she developed new-onset dyspnea as well as Takotsubo cardiomyopathy. Intravenous methylprednisolone 500 mg/day was administered for 3 days followed by transition to intravenous dexamethasone and slow tapering to prednisolone. Prednisolone was gradually tapered and eventually discontinued after 3 months. Conclusions: Paclitaxel-induced pneumonitis is a rare complication. The diagnosis should be considered in any patient who develops respiratory symptoms while receiving paclitaxel. Acute fibrinous and organizing pneumonitis is a rare type of interstitial pneumonitis with high recurrence and mortality rates. High-dose steroids are needed to treat this type of pneumonitis.